Pengaruh Komite CSR Terhadap ESG Disclosure Dengan Dewan Komisaris Perempuan Sebagai Variabel Moderasi Pada Perusahaan Tambang - Latifatul Ariqoh; Evi Ekawati; Ahmad Hazas Syarif (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2026)
Environmental, Social, and Governance disclosure is a critical aspect of ensuring corporate sustainability, particularly in the mining sector. One governance mechanism frequently highlighted in improving the quality of sustainability disclosure is the presence of a CSR committee and a board of commissioners composed of women. Therefore, this study aims to analyze the influence of the CSR committee on ESG disclosure with a board of commissioners composed of women as a moderating variable. This study employs a quantitative approach using secondary data obtained from annual reports and corporate sustainability reports. The analysis employs descriptive statistics and was processed using IBM SPSS 25 software.